Role of apoptotic, autophagic and senescence pathways in minor salivary gland adenoid cystic carcinoma - João Augusto Vianna Goulart-Filho; Victor Angelo Martins Montalli; Fabrício Passador-Santos; Ney Soares de Araújo; Vera Cavalcanti de Araújo (BMC, 2019)
Abstract Background Adenoid cystic carcinoma (ACC) is a salivary gland malignancy with poor long-term survival, which warrants studies aimed at clarifying the pathogenesis of this disease in order to widen the scope of therapeutic options currently available. Alterations in regulatory mechanisms relating to vascular support, cell death and autophagy are important pathways for tumor growth in cancer. Thus, the present study aimed to access vascular supply, apoptosis, autophagy and cell senescence in ACC of minor salivary glands. Methods We analyzed 25 cases of minor salivary gland ACC by immunohistochemistry using anti-CD34, anti-CD105, anti-D2-40, anti-Bax, anti-Bcl-2, anti-Beclin-1, anti-LC3B, anti-p21 and anti-p16. Results Microvessel density was low and based on anti-CD34, anti-CD105 and anti-D2-40 immunostaining. There was positivity for anti-CD34, anti-Bcl-2, anti-Beclin, anti-LC3B and anti-p21 and a positive correlation between Bcl-2 and Beclin (p = 0.014). Conclusions Our results showed that ACC does not depend on neo-angiogenesis and is probably associated to anti-apoptotic, autophagic and anti-senescence events.